Voice Outcome Measures for Adult Patients With Unilateral Vocal Fold Paralysis: A Systematic Review. (19th September 2018) - Walton, Chloe; Carding, Paul; Conway, Erin; Flanagan, Kieran; Blackshaw, Helen
Abstract : Objectives: Unilateral vocal fold paralysis (UVFP) typically results in marked changes in voice quality and performance and has a significant impact on quality of life. Treatment approaches generally aim to restore glottal closure for phonation and improve vocal function. There are a wide range of voice outcome measures that are available to measure the treatment effect. Careful selection of voice outcome measures is required to ensure that they are adequate for purpose and are psychometrically sound to detect the treatment effect. This article aims to critically evaluate the literature for voice outcome measures that are used for patients with UVFP. Study Design: Systematic review. Methods: Nine databases were searched for UVFP treatment studies published since 2003 (n = 2, 484 articles). These articles and their references were screened using inclusion/exclusion criteria, including population characteristics, treatment, voice outcomes, and study findings. Data from the included articles was extracted and appraised with respect to multidimensionality, timing, selection rationale, validity, reliability, and responsiveness to change of the voice outcome measures. Results: A total of 29 studies met the inclusion criteria for the systematic review. These studies showed considerable variability in the rationale, selection, and application of voice outcome measures for reporting the treatment effect for patients with UVFP. Conclusion: There is currently a significant disparity in the selection and use of voice outcome measures for patients with UVFP. A set of principles around selection rationale, validity, reliability, and responsiveness to change is proposed to enhance the judicious selection of voice outcome measures for this patient group. Laryngoscope, 129:187–197, 2019